2021
DOI: 10.1128/aac.00321-21
|View full text |Cite
|
Sign up to set email alerts
|

Checkerboard Analysis To Evaluate Synergistic Combinations of Existing Antifungal Drugs and Propylene Glycol Monocaprylate in Isolates from Recalcitrant Tinea Corporis and Cruris Patients Harboring Squalene Epoxidase Gene Mutation

Abstract: Introduction: Recalcitrant dermatophytic infections of the glabrous skin (tinea corporis/cruris/faciei) pose a huge challenge to healthcare systems. Combinations of oral and topical drugs may potentially improve cure rates but the same has never been objectively assessed for this condition in laboratory or clinical studies.The presentstudy was undertaken with an aim of identifying synergistic combinations of oral and topical antifungals by testing clinical isolates obtained from patients with recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Thus, appropriate dosage of TRB in treatment of dermatophytosis could prevent the usage of azole drugs and development of resistance against azole-based antifungal drugs. Recently, in vitro synergistic interactions with varying combinations of ITC, TRB, ketoconazole, and luliconazole (LUZ) have been observed in TRB-resistant Indian strains [ 43 , 44 ]. However, effectiveness of TRB and ITC in combination for treatment of tinea infections in a recent randomised trial showed no added beneficial effect over treatment with ITC alone [ 45 ].…”
Section: Multidrug-resistant T Indotine...mentioning
confidence: 99%
“…Thus, appropriate dosage of TRB in treatment of dermatophytosis could prevent the usage of azole drugs and development of resistance against azole-based antifungal drugs. Recently, in vitro synergistic interactions with varying combinations of ITC, TRB, ketoconazole, and luliconazole (LUZ) have been observed in TRB-resistant Indian strains [ 43 , 44 ]. However, effectiveness of TRB and ITC in combination for treatment of tinea infections in a recent randomised trial showed no added beneficial effect over treatment with ITC alone [ 45 ].…”
Section: Multidrug-resistant T Indotine...mentioning
confidence: 99%
“…However, these guidelines have not taken into consideration the in vitro antifungal susceptibility data and therapeutic serum levels and have led clinicians into empirically prescribing high doses of ITZ for superficial dermatophytosis without conforming to the basic tenets and science of pharmacology that dictate prescription of ITZ 16 . In addition, there is a rising trend of prescribing irrational combinations of antifungals in an attempt to counter the often unsatisfactory clinical responses with ITZ, without regard to in vitro synergy data, thus further subjecting patients to drug toxicity 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, there is a rising trend of prescribing irrational combinations of antifungals in an attempt to counter the often unsatisfactory clinical responses with ITZ, without regard to in vitro synergy data, thus further subjecting patients to drug toxicity. 17,18 Therapeutic drug monitoring (TDM) has been widely utilised for prophylactic and therapeutic use of ITZ in systemic mycoses.…”
mentioning
confidence: 99%
“…When tested alone, the compound presented an MIC of 626.62 µM and nystatin presented an MIC of 8.0 µM. When tested in combination, compound 6 presented an MIC of 313.31 µM and nystatin presented an MIC of 3.2 µM, thus demonstrating an additive effect (0.5 < FIC ≤ 1); see Table 5 [ 79 ].…”
Section: Resultsmentioning
confidence: 99%